Remoteness, urbanization, and child nutrition in sub‐Saharan Africa. (20th September 2018) - Headey, Derek; Stifel, David; You, Liangzhi; Guo, Zhe
Abstract: Rural populations face a much higher burden of child undernutrition than urban populations, especially in sub‐Saharan Africa, a continent where many households still live in remote rural areas. Despite this, relatively little research has analyzed nutrition differences across rural and urban populations, or across gradients of rural remoteness. In this article, we study these differences in sub‐Saharan Africa by linking spatial data on travel times to urban centers with 20, 000 or more people as our measure of remoteness to Demographic Health Survey data covering 74, 398 children from 10, 900 communities in 23 countries. We find that children in rural communities have much worse linear growth and dietary outcomes than urban children, but that children in more remote rural communities face only a small nutritional penalty compared to children from less remote communities. Moreover, the harmful effects of remoteness and rural living largely disappear once we control for education, wealth, and social/infrastructural services. This implies that the key nutritional disadvantages faced by rural populations stem chiefly from social and economic poverty. Combating these problems requires a combination of innovative cost‐effective mechanisms for extending basic services to isolated rural communities and facilitating welfare‐enhancing migration to urban areas.